PENGEMBANGAN BAHAN AJAR MATA PELAJARAN AKUNTANSI PERBANKAN DAN KEUANGAN MIKRO BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) - Novandhi Setyawan Putra; Rochmawati Rochmawati (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2020)
ABSTRACTThis study included in R&D (Research and Development). Development model using 4-D from Thiagarajan, Semmel, and Semmel, namely define, design, and develop. However, disseminate stage is not carried out. The goal of this development research is to produce products of teaching materials bank accounting and micro finance based on Contectual Teaching and Learning (CTL), and to analyze feasibility of teaching material products. To analyze the feasibility of teaching materials, researcher uses review and validation sheet as the instrument of review activity. The reviewers and validators  of the material done by teachers of SMKN 10 Surabaya and lecturer of Accounting Education UNESA, linguistic by lecturer of language department UNESA, and graphics by lecturer of Educational Technology department of UNESA.  The results of this study show that material eligibility and content presentation obtain 86% with very feasible criteria, language eligibility obtain 80% with feasible criteria, graphics eligibility obtain 98,9% with very feasible criteria and the average eligibility of teaching materials obtain 88,3% with very feasible criteria. Kata Kunci: Bahan Ajar, Contextual Teaching and Learning (CTL), Akuntansi Perbankan dan Keuangan Mikro